Carvedilol-Induced Hyperkalemia in a Patient With Chronic Kidney Disease. (February 2015) - Hahn, Lindsay; Hahn, Martin
A 69-year-old male was admitted to the hospital with a chief complaint of abdominal pain, nausea, and vomiting. He had an extensive past medical history, including diabetes mellitus type 2 and chronic kidney disease stage III. Prior to admission, the patient was taking carvedilol 3.125 mg twice daily with no abnormality in his serum potassium. During hospitalization, his carvedilol was increased to 6.25 mg twice daily. The patient's serum potassium then rose from 4.8 to 6.7 mEq/L, with no improvement following administration of sodium polystyrene sulfonate. Nephrology concluded the carvedilol could be contributing to the hyperkalemia. The dose was decreased back to 3.125 mg twice daily, leading to the potassium normalizing to 4.4 mEq/L. The reported incidence of beta-blocker–induced hyperkalemia is less than 5%. A literature search revealed several cases of beta-blocker–induced hyperkalemia, but to the authors' knowledge, this is the first case describing carvedilol specifically. Utilization of the Naranjo probability scale indicated a possible probability that the carvediol was the cause.